Communication Skill Training for Female Online Ojek Drivers - Agustina, Tri Siwi; Khant, Thant Thet Oo; Meilinawati, Neni (Faculty of Education Universitas Negeri Malang, 2024)
Doing online motorcycle taxi work is required to not only be able to drive motorized vehicles, but also requires various skills and techniques to become a successful online motorcycle taxi driver, including communication skills. Communication Skill Training is aimed at 26 female online ojek drivers in the city of Surabaya. The method of implementing community service activities is experiential learning in the form of practice and also interspersed with lectures. The results of the observation occurred a change in the attitude of the participants in communicating, for example, being more confident and wiser in word selection. In addition, the experiential learning method has proven effective for changing attitudes and improving partner communication skills.